Pemasaran Umkm Produk Lokal Dengan Pemanfaatan Sistem Berbasis Web Menggunakan CMS Wordpress - Marina Elsera; Diana Suita; Simon Petrus Simorangkir; Johan Oberlyn Simanjuntak (Jurnal TUNAS, 2022)
This study aims to develop a source of promotion for a local UMKM online through a website. Not only promotion through social media, marketing through website media is also expected to be able to advance UMKM business in ordering various small and large parties. The UMKM that will be developed through the creation of this website is the Home Industry Polo Stato, which manufactures various types of men’s bags. This Home Industry requires promotional media that must be further improved because it still uses promotional media in the form of social media such as Whatsapp, and Facebook to through information sources from person to person. The application of the CMS WordPress application to UMKM can increase sales and expand the range of promotions and can also be used for promotional media on Polo Stato.